(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This study aims to understand the extent to which civic bots constitute an activist communication repertoire on Twitter, based on an analysis of Brazilian initiatives. The hypothesis explored by this article is that these initiatives have simultaneously helped to establish a professional field, related to the datafication of civil society organizations and data journalism, and also to form specialized audiences. Based on approximately 130,000 tweets that mention or react to at least one of 14 different civic bots in Brazil, over the last five years, the investigation aims to (1) identify possible networks of actors that occur among the audiences, and (2) compare the reach and effects of each initiative. The initial results indicate the existence of a group of users extremely engaged in interacting with these tools.